1999
DOI: 10.1161/01.cir.99.11.1458
|View full text |Cite
|
Sign up to set email alerts
|

QT Dispersion as an Attribute of T-Loop Morphology

Abstract: QTD is an attribute of T-loop morphology, as expressed by T-loop amplitude and width.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
121
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(128 citation statements)
references
References 33 publications
6
121
1
Order By: Relevance
“…Indeed, several reports show that in patients with acute myocardial infarction or Behçet's disease, QT dispersion is associated with LV dilation and deterioration of diastolic function (20,25,28). However, Kors et al suggested an important point that at all electrode sites, repolarization potentials must have principally the same duration by simple electric field theory (29). Other studies also suggested that QT dispersion is an attribute of T-loop morphology or projection effect (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several reports show that in patients with acute myocardial infarction or Behçet's disease, QT dispersion is associated with LV dilation and deterioration of diastolic function (20,25,28). However, Kors et al suggested an important point that at all electrode sites, repolarization potentials must have principally the same duration by simple electric field theory (29). Other studies also suggested that QT dispersion is an attribute of T-loop morphology or projection effect (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…40 QT interval dispersion is no longer believed to represent spatial inhomogeneity of repolarization throughout the ventricular myocardium, 13 as originally proposed. 1 Several recent studies 41,42 have demonstrated that it probably indicates a global ventricular repolarization abnormality, reflected by an altered, more complex, spatial vectorcardiographic T-wave loop, as would be expected to occur in the hypertrophied myocardium with increased interstitial fibrosis. This is the most probable explanation, we think, for the observed association between LVM and QT interval dispersion.…”
Section: Discussionmentioning
confidence: 99%
“…32 This only adds further to the growing impression that even though QT dispersion to a certain point does reflect ventricular repolarization, future effort should be made to express repolarization abnormalities in other and more reproducible manners, also with regard to survival analysis.…”
Section: Discussionmentioning
confidence: 99%